Comparative analysis of Nader Ardalan's vision based on post-modern features - Fataneh Sangtarash; Hasan Ali Pourmand (طراحی و برنامه ریزی در معماری و شهرسازی)
Recognition and analysis of the works of contemporary architects in Iran is of particular importance, in this regard, the concepts of the influence of Western architecture on the thought of Iranian architects and the evolution of modern, modern and postmodern styles and the differentiation of each of these styles have a significant impact on the recognition of the works of architects such as Nader Ardalan. Reviewing the works and thoughts of Iranian architects in the post-modern period indicates the existence of an attempt to find the relationship between the architecture of Iran yesterday and today. The most important goal of this article is essays about the vision of Nader Ardalan as an author architect based on the characteristics of post-modern style. With the assumption that the vision of Nader Ardalan in the works left by him has an impact on Iran's post-modern style, in this research, it will answer the research question with a comparative research plan. In this paper, first the postmodern style has been studied, then Nader Ardalan's works have been analyzed according to the postmodern style, and some features are considered according to the Jenks table including ideology, style and design idea, and finally similarities of Ardalan's works with postmodern features have been analyzed. The research results of his works show his adherence to tradition in spatial arrangement and organization of volumes and forms. It can be said that most of Nader Ardalan's works have features of postmodern style. In terms of purpose, more traditionalism and historicism of the climate can be pointed out, and in terms of design ideas, the use of traditional Iranian architecture pattern and the use of rectangle, square, and central courtyard elements.